Access to education and labor market in sub-saharan Africa - (:unkn) unknown (My University, 2018)
Compared to other regions, sub-Saharan Africa lags far behind in terms of poverty reduction and human development. This is partly explained by the low access to education combined with the weak dynamism of the labor market, characterized by a large share of vulnerable employment. In 2016, one in three children in sub-Saharan Africa is out of school and more than seven out of ten workers are employed in vulnerable jobs. This thesis proposes three empirical studies to better understand, on the one hand, access to education in sub-Saharan Africa and, on the other hand, the impact of access to a decent job on poverty reduction. Chapter 1 examines the role of social interactions in schooling decisions in rural Senegal using data from a demographic surveillance system. This study uses the caste system in Senegal and geographical proximity to build social groups. Results show that the membership to a social group strongly influences school attendance. Three mechanisms could explain this effect: social norms, the perception of return to education, and ripple effects. Chapter 2 aims to analyze whether orphans on the one hand, and non-orphans not living with their biological parents on the other hand, are disadvantaged in terms of access to education and child labor. I use data from a panel survey collected in rural Tanzania. The results show that paternal orphans and double-orphans receive less education expenditure but are not disadvantaged in terms of schooling or child labor. On the other hand, paternal orphans residing with their mothers receive on average the same amount of education expenditure as other children and are more likely to attend school. On average, non-orphaned fostered children are not different from children living with their biological parents in terms of education and child labor. These findings suggest an absence of discrimination against orphans and fostered children, but a loss of income for paternal orphans which could impede their ed
Keywords: African Research